PERANAN FILSAFAT HUKUM DALAM MEWUJUDKAN KEADILAN - Muh. Rizal R. Dekol; Surajiman Perkasa (INTELIGENSIA MEDIA, 2022)
This paper intends to deepen the study of the role of Legal Philosophy in realizing justice. However, if there is a question of fairness, it cannot be determined what steps are used to determine whether something is fair or not. Various answers about justice are usually never or rarely satisfactory, so they continue to be debated, so it can be concluded that various formulations of justice are relative statements. This problem ultimately encourages many people to take shortcuts by leaving the formulation or justice to legislators and judges who will formulate it based on their own considerations.